Nationality, Locality, and Religiosity: Works and Thoughts of Maria Theresia Geme of the Forum for Religious Harmony of East Nusa Tenggara - Rohmawati, Wiwin Siti Aminah; Cholil, Suhadi; Udasmoro, Wening (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This article examines Maria Theresia Geme's thoughts and works on the issue of religious harmony through Forum for Religious Harmony (FKUB) of East Nusa Tenggara (NTT). This is a qualitative study which gathers data through observation, in-depth interviews, and document analysis. This research aims to address three primary questions: (1) How the agency of "women's leadership" of Maria T. Geme within FKUB NTT?; (2) What is her perspective on women's involvement in issues of  religious harmony and peace building?; (3) What are Maria  thoughts and works while leading FKUB NTT, and what it's implications for interfaith dialogue and religious harmony? This study concluded that Geme is the first and only woman in the history of Indonesia to lead FKUB at the provincial level. Her leadership strategy is to integrate women's leadership and her agency in the development of FKUB initiatives, in order to emphasizes women's involvement on the issue of religious harmony with mubadalah paradigm (mutuality). For Geme, the Indonesian identity will be strengthened through a balanced relationship between religious values and local wisdom. Therefore, preserving and strengthening local wisdom is one of important things in developing and fostering interfaith dialogue and religious harmony.